Concomitant Persistent Left Superior Vena Cava and Horseshoe Kidney - Faraz Jaffer; Vijay Chandiramani (Case Reports in Nephrology)
Persistent left superior vena cava (PLSVC) and horseshoe kidney (HSK) are common congenital abnormalities; however presence of both in the same person is extremely rare. A patient with hepatitis C cirrhosis awaiting transplant presented with worsening liver dysfunction, diagnosed with acute renal failure secondary to hepatorenal syndrome, and required X-ray fluoroscopy guided tunneled venous catheter placement for hemodialysis. Review of imaging studies demonstrated coexistence of PLSVC and HSK. PLSVC in adulthood is usually incidental with the most common drainage pattern being without physiologic dysfunction. Isolated horseshoe kidney is still the most common of renal fusion anomalies; however etiology of coexistent PLSVC remains unknown.